Carbon (CO2) Footprint Reduction Analysis for Buildings through Green Rating Tools in Malaysia. (May 2017) - Ramachanderan, Surenthira Stephen; Venkiteswaran, Vinod Kumar; Chuen, Yap Tze
Abstract: This study aims to identify and discuss the Green House Gas (GHG) emission reduction through Green Rating Tools in Malaysia in recognition of the environmental and economic threats posed by climate change. One sector receiving particular attention worldwide is the building industry that has grown significantly and responsible for more than 40 percent of global energy use. As much as one third of global GHG emissions, both in developed and developing countries are from building energy use. In view of this, the global community has taken various measures to mitigate the impact which includes the call for reduction of fossil fuel through energy efficiency and substitution of renewable energy, encouraging the building industry to adopt construction of sustainable buildings known as green buildings (GB). Green building focuses on increasing the efficiency of resource use – energy, water, and materials – while reducing building impact on human health and the environment during the building's lifecycle, through better siting, design, construction, operation, maintenance, and removal. GB is certified through Green Rating Tools (GRT) to establish energy savings and GHG emission reductions.